Methanogenic archaea diversity in hyporheic sediments of a small lowland stream. (April 2015) - Brablcová, Lenka; Buriánková, Iva; Badurová, Pavlína; Chaudhary, Prem Prashant; Rulík, Martin
Abstract: Abundance and diversity of methanogenic archaea were studied at five localities along a longitudinal profile of a Sitka stream (Czech Republic). Samples of hyporheic sediments were collected from two sediment depths (0–25 cm and 25–50 cm) by freeze-core method. Methanogen community was analyzed by fluorescence in situ hybridization (FISH), denaturing gradient gel electrophoresis (DGGE) and sequencing method. The proportion of methanogens to the DAPI-stained cells varied among all localities and depths with an average value 2.08 × 10 5 per g of dry sediment with the range from 0.37 to 4.96 × 10 5 cells per g of dry sediment. A total of 73 bands were detected at 19 different positions on the DGGE gel and the highest methanogen diversity was found at the downstream located sites. There was no relationship between methanogen diversity and sediment depth. Cluster analysis of DGGE image showed three main clusters consisting of localities that differed in the number and similarity of the DGGE bands. Sequencing analysis of representative DGGE bands revealed phylotypes affiliated with members belonging to the orders Methanosarcinales, Methanomicrobiales and Methanocellales. The knowledge about occurrence and diversity of methanogenic archaea in freshwater ecosystems are essential for methane dynamics in river sediments and can contribute to the understanding of global warming process. Highlights: We examine diversity and identification of methanogens along a longitudinal stream profile. Methanogen diversity increased from upstream to downstream. We report the presence of hydrogenotrophic and acetoclastic methanogens.